Five years of treatment for retinopathy of prematurity in Sweden: results from SWEDROP, a national quality register. Issue 12 (11th March 2016) - Holmström, Gerd; Hellström, Ann; Jakobsson, Peter; Lundgren, Pia; Tornqvist, Kristina; Wallin, Agneta
Abstract : Background/aims: Retinopathy of prematurity (ROP) is a sight-threatening disease, requiring efficient screening and treatment. The present study aims to describe various aspects on treatment for ROP in Sweden. Methods: Data on treatment for ROP in infants born in 2008–2012 were extracted from Swedish national register for retinopathy of prematurity, a web-based national register. Results: During 2008–2012, 3488 infants with a gestational age (GA) at birth of <31 weeks had been screened for ROP in Sweden. Altogether, 30.3% (1057/3488) of the infants developed ROP and 5.2% (181/3488) were treated. Type 1 ROP was found in at least one eye in 83.2% (149/179) of the treated infants. One third of the eyes (32.2% right, 29.9% left eyes) were treated more than once. Laser was the only treatment in 90% of the eyes. Mean number of laser spots at first laser session was 1177 and 1386 in right and left eyes, respectively. Number of laser spots correlated negatively with GA at birth (p=0.01). There was no change in frequency of treatment or number of laser spots during the 5-year period. Anti-vascular endothelial growth factor injections were performed in 28 eyes, encircling band was used in five eyes and vitrectomies were performed in seven eyes. Twenty-six retinal surgeons performed 9.4 (range 1–37) treatment sessions in the 181 infants. Conclusions: The present study reveals similar incidences of ROP and frequencies of treatment during the 5-year study period. Many surgeons were involved in treatment of a rather limited number of infants. The results call for national discussions on organisation of ROP treatment.